The Differences of Feed Quality and Egg Production Performance of Tegal and Magelang Ducks on Farming in Central Java - Ismoyowati Ismoyowati; Diana Indrasanti; Ibnu Hari Sulistyawan (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This study was conducted to compare the environmental conditions around farms which was located in Tegal for Tegal ducks and Magelang for Magelang ducks. This study was also aimed to compare the composition of both feed nutrient content and the egg production. The research was conducted by survey method with purposive random sampling based on duck populations and age (8-15 months) provided by the farmer. Each area was provided 10 farmers for every farm and the data were collected in July-September, 2017. Environmental condition measurement were the temperature of the duck housing, and the composition and nutrient content of feed and the egg production of ducks. The results showed that all farmers’ ducks on a dry system rearing (without water pool) with average temperature in Tegal area 30.53±1.38oC and Magelang 28.32±1.00oC. Feed compositions given for Tegal duck consist of: dried rice, rice bran, concentrate, trash fish, golden snail, vermicelli waste and shrimp waste. The average nutrient content was crude protein 19.25%, energy 2,913 kcal/kg, crude fiber 5.82%, crude fat 6.87%, Ca 3.06% and P 1.40%. Feed composition for Magelang ducks consisted of rice (nasi aking), rice bran and concentrate, with crude protein content of 17.99%, 2,801 kcal/kg, crude fiber 8.14%, crude fat 6.10%, Ca 2.29% and P 1.04%. Tegal duck egg production was lower than Magelang ducks (64.89 vs 75.44%), but the egg weight was relatively the same. It could be concluded that the temperature of Tegal duck housing in Tegal region was hotter than Magelang region. Although the food quality of Tegal ducks was better than that of Magelang ducks, Tegal duck had a lower egg production because of the high environmental temperature.